PENGARUH KUALITAS LAYANAN KOMUNIKASI PEMASARAN DAN KOMITMEN TERHADAP KEPUASAN NASABAH PD BPR BAHTERAMAS KABUPATEN WAKATOBI - La Evi; Sudirman Zaid; Nursaban Rommy Suleman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to: 1) examine the simultaneous effect of service quality, marketing communication and commitment on customer satisfaction, 2) examine the effect of service quality on customer satisfaction, 3) examine the effect of marketing communication on customer satisfaction, 4) examine the effect of commitment on customer satisfaction.The object of research is the Regional Company BPR Bahteramas Wakatobi. The research population is the customers or debtors of BPR Bahteramas Wakatobi, totaling 304 respondents. The sampling technique uses the Slovin formula with a precision of 10 percent, thus the research sample is 75 respondents.The data collection method used a questionnaire and all samples returned the submitted questionnaire. The research data was processed using multiple linear regression analysis using the SPSS Ver 22 device.The results of the study: 1) simultaneously service quality, marketing communication and commitment have a significant effect on customer satisfaction, 2) service quality has a positive and significant effect on customer satisfaction, 3) marketing communication has a positive and significant effect on customer satisfaction, 4) customer commitment has a positive effect and significant to customer satisfaction.